2015
DOI: 10.1007/s10162-014-0499-z
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Temporal Modulation Detection in Normal-Hearing and Cochlear Implanted Listeners: Effects of Hearing Mechanism and Development

Abstract: Temporal modulation detection ability matures over many years after birth and may be particularly sensitive to experience during this period. Profound hearing loss during early childhood might result in greater perceptual deficits than a similar loss beginning in adulthood. We tested this idea by measuring performance in temporal modulation detection in profoundly deaf children and adults fitted with cochlear implants (CIs). At least two independent variables could constrain temporal modulation detection perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 82 publications
3
19
1
Order By: Relevance
“…sensitivity to broadband intensity modulation develops more slowly in pre-lingually deaf CI users than in NH listeners (Park et al, 2015). The inconsistency between the present findings and the work of Park et al has several possible explanations.…”
Section: B Across-channel Intensity Resolution and Srdcontrasting
confidence: 97%
See 2 more Smart Citations
“…sensitivity to broadband intensity modulation develops more slowly in pre-lingually deaf CI users than in NH listeners (Park et al, 2015). The inconsistency between the present findings and the work of Park et al has several possible explanations.…”
Section: B Across-channel Intensity Resolution and Srdcontrasting
confidence: 97%
“…These results were not expected, but in retrospect, are consistent with the reduced dynamic range of electric versus acoustic hearing. However, Park et al (2015) found no significant relationship between electrical dynamic range of their participants' clinical maps and amplitude modulation sensitivity. Given that patients were using their clinical processors and preferred settings, the relative influence of neural intensity coding and signal processing/compression on this effect cannot be determined in the present study.…”
Section: B Across-channel Intensity Resolution and Srdmentioning
confidence: 74%
See 1 more Smart Citation
“…There are many factors that are known to affect performance when hearing through a cochlear implant, for example age correlates both with acoustical hearing abilities as well as with central processing abilities (Gates and Mills 2005; Humes et al 2012; Jin et al 2014; Park et al 2015). Although there was significant overlap between the ages of the participants in the implanted and normal-hearing cohorts ( Table 1 ), their mean ages were different (Mann-Whitney U-test, p<0.01).…”
Section: Resultsmentioning
confidence: 99%
“…While the authors did not specifically discuss the age at which SMRT performance peaked in hearing-impaired children, a possible interpretation of this observation is that decreased access to auditory information, and the degraded auditory signal that the central auditory system receives because of hearing loss, prolongs the maturation of spectral resolving capabilities. Other prior studies with pediatric CI users have demonstrated immature temporal sensitivity ( Jung et al., 2012 ) and intensity resolution ( Park, Won, Horn, & Rubinstein, 2015 ) in school-age children and adolescents compared with adults with CIs.…”
Section: Introductionmentioning
confidence: 97%